(untitled) (Journal of Health Sciences, 2013)
Introduction: The role of hyperhomocysteinemia in psychotic disorder can be explained by partial antagonism of homocysteine on NMDA-glycine receptor. Plasma concentration of homocysteine is an indicatorof the status of the B-vitamins (folate, B12, B6). Folate deficiency may have different effects on the neurochemical processes of schizophrenia. This suggests that the association between elevated levels of homocysteine and schizophrenia is biologically very likely.Methods: The study was consisted of 20 patients with schizophrenia and 20 healthy controls. We investigated the levels of serum homocysteine concentration using AxSYM (Abbott), levels of folate assay istwo-step immunoassay to determine the presence folate in human serum using CMIA (chemiluminescent microparticle immunoassay) technology and Axsym Holo Tc is microparticle enzyme immunoassay (MEIA)for the quantitative determination of human holo TC in serum and determination defi cit of vitamin B 12.Results: The patients group has higher levels of homocysteine in compare with controls group for 3.85 μmol/L while the concentration of folate in the group of patients was lower for 9.17 ng/mL. The mean level of vitamin B-12 in investigation groups were in reference range 19.1-119 pmol/L, but patient group have lower average concentration of vitamin B-12 lower for 24.81 pmol/L compared to the control group.Conclusion: Our results showed that homocysteine concentration is inversely proportionate to folate concentration,i.e. as homocysteine concentration in serum increases, folate concentration falls. Shizophrenicpatients with elevated tHcy level and low folate levels should have vitamin supplementation with folic acid.